HUBUNGAN PENGETAHUAN TENTANG HIPERTENSI DENGAN PERILAKU PENCEGAHAN KEKAMBUHAN HIPERTENSI PADA LANSIA - Caroline, Sarah; Arneliwati, Arneliwati; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hypertension is a degenerative disease that many elderly people experience is the increase in blood pressure beyond the normal limit. Elderly is one group that has a high risk of hypertension In the elderly there is an aging process where the elderly experience a decrease in intellectuality which includes cognitive abilities, perception, and memory so that the elderly are unable to remember knowledge in preventing hypertension recurrence. This study aims to determine the relationship of knowledge about hypertension with prevention behavior of hypertensive relapse in elderly in Kelurahan Pesisir Working Area of Puskesmas LimaPuluh. This study uses a descriptive correlation design with a cross sectional approach. The sample of the research were 58 respondents taken based on the inclusion criteria using total sampling technique. The measuring tool used is the questionnaire. The result of this study showed that elderly people have poor knowledge about hypertension as much as 27 respondents (46,6%), and bad behavior in prevention of hypertension relapse 22 respondent (81,5%). The result of chi square test shows that there is correlation of knowledge about hypertension with hypertension relapse prevention behavior in elderly p value = 0,001 (p < 0,05). It is recommended that the elderly so that the elderly understand good behavior in a healthy life behavior and the elderly are expected to take the time to check blood pressure regularly so as to prevent recurrence of more severe hypertension. Key words: Attitude prevention behavior, elderly, hypertension, knowledge